(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
Optic nerve glioma is a slow-growing tumor that usually occurs more often in children. 30% of patients with this diagnosis also have associated NF1 (neurofibromytaosis type 1) and have a better prognosis. Malignant gliomas (glioblastomas) are rare and almost always occur in adult men, with a poor prognosis and certain death within one year. Optic nerve gliomas account for about 1% of all intracranial tumors. About 10% of optic pathway tumors are located within the optic nerve. One third of tumors affect both the optic nerve and the chiasm, another third primarily affects the chiasm itself, and one fourth is localized primarily in the hypothalamus. Only 5% of gliomas are multicentric.]..